Sounds of fiction: Songs in the teaching and learning of English and literature / Mohd Rozaidi Ismail ... [et al.] - Ismail, Mohd Rozaidi; Abdul Aziz, Roslina; Abas, Nadhratunnaim; Nikman, Khairunisa (Universiti Teknologi MARA Cawangan Pahang, 2020)
Teaching literature to language learners can be daunting. One of the ways to ensure fun and effective learning is through the incorporation of music or songs in the language classroom. Numerous studies have confirmed the benefits of music or songs in improving learners' text recall ability and reducing their anxiety. Regardless, the studies have also pointed out a mismatch between teachers' positive feedback on their incorporation in the language classroom and the actual teaching practice due to some limitations such as lack of resources in finding suitable syllabi-based music or songs and inadequate preparation time. Hence, to overcome these limitations, the present study intends to propose literature-based lyrics of The Necklace, a short story by Guy de Maupassant. The effectiveness of these lyrics have been pilot-tested on a group of language teachers in Kastamonu, Turkey. The results indicate that not only that these teachers are willing to use the lyricised literature in their classroom, but they also agree on its effectiveness in improving comprehension and text recall.